Climate Change and Human Migration: Towards More Humane Interpretation of Refugee - Sarjana, I Gede Eka (Udayana Journal of Law and Culture, 2018)
This article seeks to highlight the existing 1951 Convention relating to the Status of Refugees (hereinafter referred to as Refugee Convention) and the possibilities of the document to encompass climate-induced migration by modifying, reconstructing and establishing a specific legal regime, considering that the concept of Internally Displaced Persons (IDPs) has been inadequate and incapable to incorporate the ‘newly introduced’ type of migrant. The definition of refugee in the Convention explicitly limits the scope of people who are forced to flee their home into migrants due to warfare and civil disturbance. In fact, there are people who can no longer gain decent livelihood due to environmental and social problems including poverty, drought, soil erosion, desertification, deforestation, floods and other environmental deterioration. However, these people have not been legally accepted as ‘refugee’ in the international arena. The author argues that ‘environmental refugee’ or ‘climate refugee’ is a clear and present issue, as climate change-related disasters are rampant and deteriorating. Therefore, this article will examine the existing and potential role of international law in effectively responding to climate change and its related humanitarian problems in the future. The development of a specific legal document on environmental refugee and the global acceptance of the status of the people not only represent a short-term solution for the affected people, but also introduce a long-term commitment of international community to alleviate poverty and guarantee the fulfilment of basic human rights and social justice for everyone. This article primarily investigates relevant legal documents and discovers some legal and non-legal concepts that are connected to the central topic of this article .